Efektivitas Audit Kinerja Sektor Publik Dalam Mewujudkan Good Governance Melalui Akuntabilitas Pengelolaan Keuangan Publik - Dito Nst; Melia Fauzia; Mhd. Rizki; Nabilah Surahman; Nurmayani (Penerbit Jurnal Indonesia, 2026)
This research examines the effectiveness of public sector performance auditing in promoting good governance through accountability in public financial management. Transparent, accountable, effective, and participatory public financial management is a crucial factor in achieving good governance) (however, its implementation in Indonesia still faces several challenges, including weaknesses in internal control systems, low program effectiveness, and inadequate follow-up on audit recommendations. This study aims to analyze the role of public sector performance auditing in strengthening accountability and improving the quality of government governance. The research employs a descriptive qualitative approach based on a literature review, with secondary data collected from audit reports issued by the Audit Board of Indonesia (BPK) and the Finance and Development Supervisory Agency (BPKP), national regulations, and scholarly journals related to public sector auditing, accountability, and good governance. The findings indicate that performance auditing plays a significant role in enhancing accountability in public financial management, assessing the effectiveness, efficiency, and economy of budget utilization, and providing recommendations for policy improvement. Nevertheless, the effectiveness of performance auditing remains constrained by limited auditor capacity, weak internal control systems, and low levels of follow-up on audit recommendations. Future efforts are expected to optimize performance auditing through improvements in auditor competence and workforce size, stronger commitment from government institutions to implement audit recommendations, and the development of more effective internal control systems, thereby enabling the sustainable realization of good governance